Whisper of the heart [videorecording (DVD)] - Hirakawa, Yūichirō; Seino, Nana; Matsuzaka, Tori; Araki, Towa; Hiiragi, Aoi, 1962- (MPI Home Video, 2023)
Two third grade students, Shizuku and Seiji, form a special friendship and each make a vow to pursue their respective dreams. After ten years, their paths begin to separate them geographically, and maintaining their relationship grows ever harder.